The integration of Education for Sustainable Development (ESD) in design and technology subject: through teacher’s perspective - Rosman, Rabbiatul Natrah; Omar, Muhd Khaizer; Zahari, Zulhazmi (Asian Journal of Assessment in Teaching and Learning, 2019)
The revolution and development of technology have influenced the relationship among people, society, environment, and socio-economy. This issue plays a crucial role in prospering the quality of future grassroots of the nation on the term of values, attitudes, and moral development. Education is a tool that thrives and imparts value-based education, starting from early education. Therefore, to upbringing the aforementioned mission, we employ a phenomenological study to explore the perception and opinion among Design and Technology (DNT) teachers in embedding Education for Sustainable Development (ESD) elements among primary school students. This study focuses on the teacher’s pedagogical approach in the classroom contexts and teachers’ readiness in the implementation of ESD, comprises of three main elements: environment, social, and economical. The formulated research question for this study is what teachers’ views are and how they perceive ESD as part of the subject. Qualitative research was conducted to illustrate the perception and understanding of ESD elements in DNT subjects. Selected participants are among the Head of DNT Panels and at the same time, teach DNT as their major subject. The data were collected using semi-structured interviews. Informants’ views and feedback were derived and transcribed using Nvivo software. The theme emerged from the constant comparative analysis were triangulated with secondary data; for example, field observation, memo, journals, and teacher's lesson plan. Analysis of the data indicated that student-centered learning as the theme implemented by most participants to impart ESD through student’s learning activities. Education is the optimal mechanism to disseminate ESD and encouraging learners in moral values.